Artistic treatment of animation scenes in feature films (Al-Academy, 2024)
The research deals with how to treat animation scenes within realistic events and places, in addition to the fact that this film is a narrative film and the events do not contain any kind of imagination or fantasy. The introduction of animated scenes into this type of film is due to the presence of a number of requirements within the story that must be manufactured. In the form of an animation, for example, imagining an animal and controlling its actions and reactions within the feature film or a specific accessory. Hence, the creator of the work must find artistic treatments within the work, as the researcher began with the research problem that ended with the following question: (How to achieve artistic treatment of the animated scenes in the film novelist?), then (the importance of the research, the goal of the research, the limits of the research, defining the terminology) and then the theoretical framework, which contained two sections, the first was(How to achieve the artistic treatment of animation scenes in a feature film?) Then (the importance of the research, the goal of the research, the limits of the research, defining the terminology) and then the theoretical framework, which contained two sections, the first was (artistic treatments of the elements of film expression), which dealt with the most important expressive elements In the film and its aesthetic, semantic and dramatic functions, and then the second section was (Animation... the concept and operation). The researcher deals with the concept of animation and the methods of operation within the film work, reinforced by a number of sources and references. The researcher concluded the theoretical framework with a number of indicators. And then the research procedures, which included: (Research method, research population, research sample, research tool). Then the researcher analyzed the selected sample of the foreign film: The Call of the Wild. Year of production: 2020. When the researcher reached the following results after analyzing the sample:1. Animation scenes are able to participate in presenting film events in a convincing way that is very close to the dramatic scenes in a cinematic film.2. Using animation scenes to embody some supernatural actions at the level of characters’ actions or visual effects at the level of the spatial environment.3. Animation scenes embody animal characters regardless of their formal characteristics within the structure of the cinematic film.4. Animation scenes can be used to embody and create the environment by participating in film events, whether in terms of movement, speaking, or participation in dramatic actions.5. Animation scenes overlap with real scenes to accomplish dramatic actions in a way that makes it difficult to recognize the digital technologies that created these scenes in the virtual environment technology.6. Digitally manufactured characters appear inside animation scenes, regardless of whether they are animals, human, or mutants, and they express the scenes and perform actions, and this deepens the significance of the dramatic embodiment of film events.7. The harmony and integration between the animated scene and the environment plays a role in the connection between truth and assumption within the space of the cinematic image.8. The ability of the animation viewer to embody all types of living and inanimate characters within the film space.